Contribution of micro‐PIXE to the characterization of settled dust events in an urban area affected by industrial activities - Justino, A. R. (2021)
This study aimed to identify possible sources of settled dust events that occurred in an urban area nearby an industrial park, which alarmed the local population. Settled dust was collected in January 2019 and its chemical characterization was assessed by micro-PIXE, focusing on a total of 29 elements. Comparison with chemical profiles of particulate matter from different types of environment was conducted, along with the assessment of crustal enrichment factors and Spearman correlations, allowing to understand which sources were contributing to this settled dust event. A nearby industrial area’s influence was identified due to the contents of Fe, Cr and Mn, which are typical tracers of iron and steel industries.